PELAYANAN STAF BOARDING GATE CITILINK BERDASARKAN MANAJEMEN ISLAM DI YOGYAKARTA INTERNATIONAL AIRPORT - Hidayatullah; Purwanta (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2024)
This study aims to analyze the service of Citilink's boarding gate staff at Yogyakarta International Airport based on Islamic management. The research method used is qualitative with a case study approach. Data collection was conducted through interviews, observations, and documentation. The results show that Citilink's boarding gate staff at YIA are able to organize and manage boarding procedures quickly and efficiently, allowing passengers to board the aircraft on time without any hindrance. The staff's compliance with established SOPs is a major factor supporting passenger satisfaction. In addition to compliance with SOPs, other supporting factors in improving service quality include the availability of additional facilities that facilitate staff performance. However, this study also identifies several inhibiting factors, such as operational aircraft issues causing delays and passenger dissatisfaction with staff services. To address these obstacles, this study proposes several solutions, one of which is providing compensation to passengers in case of delays as a form of responsibility and fairness. In general, the service aligns with the principles of Islamic management, such as shiddiq (honesty), amanah (trustworthiness), tabligh (good communication), and fathanah (intelligence). However, there are still some aspects that need improvement, such as empathy and responsiveness in serving passengers.